2008
DOI: 10.1177/089686080802800214
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Usefulness of Peritoneal Dialysis Fluids with Neutral pH and Low Glucose Degradation Product Concentration: An Open Randomized Prospective Trial

Abstract: Background Long-term peritoneal dialysis (PD) is associated with the development of various structural and functional changes to the peritoneal membrane when bioincompatible conventional peritoneal dialysis fluids (PDFs) are used. In this study, we looked at patients that were treated with conventional PDFs and then changed to novel biocompatible PDFs with a neutral pH and a low concentration of glucose degradation products (GDPs) to investigate whether this change could result in the arrest or reversal of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 35 publications
3
63
1
Order By: Relevance
“…There was no effect on systemic inflammatory markers and peritoneal transport remained stable. This observation is in line with several but not all studies, which, however, did not include icodextrin solution‐treated patients.…”
Section: Discussionsupporting
confidence: 88%
“…There was no effect on systemic inflammatory markers and peritoneal transport remained stable. This observation is in line with several but not all studies, which, however, did not include icodextrin solution‐treated patients.…”
Section: Discussionsupporting
confidence: 88%
“…52 A large Korean study showed lower mortality rates in patients using lactate-buffered, neutral pH, low-GDP solutions compared with standard lactate solutions; furthermore, when they used a multivariate Cox regression model, including age, diabetes, and gender, the survival advantage of the more biocompatible solution persisted. 96 In a 3-year prospective, albeit not randomized study, mortality was also determined to be lower with a biocompatible solution that had a pH of 7.4 and low GDP content compared with a standard dialysis solution. 72 Cumulatively, these studies suggest that the newer, more biocompatible solutions may decrease mortality, but more prospective, randomized studies are required for confi rmation.…”
Section: Survivalmentioning
confidence: 99%
“…In another study from Korea, comparison of low-GDP and standard solutions also provided evidence suggesting that RRF declined less rapidly with Balance compared with standard solutions. 96 However, the analysis was very underpowered and the statistical methods used for the analysis were not optimal.…”
Section: Survivalmentioning
confidence: 99%
“…In the context of the aforementioned in vitro and ex vivo studies suggesting peritoneal toxicity and perhaps even direct renal toxicity with low pH and high GDP PD solutions, several trials have been performed to evaluate the effects of NpHLGDP solutions on clinical endpoints such as membrane function, peritoneal UF and RKF. With regards to preservation of RKF, initial studies showed variable results, with some reporting benefit with NpHLGDP solutions (43,(59)(60)(61), while others found none (62)(63)(64). Among subsequently performed trials, the most promising was the balANZ randomized con- Finally, in order to circumvent the limited power of individual studies, a Cochrane review was undertaken by Cho et al (66).…”
Section: Peritoneal Membrane Function Peritoneal Ultrafiltration Anmentioning
confidence: 99%